A systematic review on bio-based phase change materials - Yadav, A.; Mahendran, Samykano; Pandey, A. K.; Tyagi, V. V.; Devarajan, R.; Sudhakar, K.; Noor, M. M. (Universiti Malaysia Pahang, 2023)
Global warming and energy depletion are the main problems faced in recent years due to energy consumption by industries and the global population. Phase change materials (PCMs) with significant properties tend to store and release energy and fill the demand and supply gap. Most organic and inorganic PCMs are not considered environmentally eco-friendly when used for thermal energy storage (TES). Because they are formed from non-conventional energy resources, their carbon footmark and environmental effect are not ignored. To reduce problems, an urgent need for eco-friendly materials is required. Green substitute bio-based phase change materials (BPCMs) have gained extensive attention and are considered the best suitable replacement for organic and inorganic PCMs because BPCMs exhibit significant properties that are cost-effective, eco-friendly, renewable and convenient for thermal energy storage. However, the thermal conductivity of BPCMs is too low, which delays TES and heat transfer rates. Furthermore, this paper summarizes the reduction of low thermal conductivity problems with the help of highly conductive nanoparticles dispersed into the BPCMs and the fabrication methods of BPCMs composites. This article also provides information for futuristic researchers about the methods of fabrication and factors for enhancing the thermal conductivity of an eco-friendly BPCM composite and draws an important conclusion from the literature.